Use of an educational DVD to explore the problem of irrational use of medicines - Shankar, PR; Mishra, P; De, A; Saha, A (Journal of Institute of Medicine Nepal, 2007)
Background: Orienting undergraduate students to the concept of rational prescribing is an important strategy for promoting rational use of medicines. The video ‘Tiim’ deals with street-sold medicines in Burkina Faso, a country in West Africa. The objectives of the study were to: a) Use the video as a platform to explore medicines use problems b) Obtain student opinion about the sessions and c) Note the association of the opinion with the respondents’ demographic characteristics. Materials and Methods: The exercise was carried out during the practical session in Pharmacology. The students were divided into groups of 7 or 8 students each and were give a set of problems. After 45 minutes the groups presented their solutions, followed by discussion and comments from the facilitators. Student feedback was collected using a structured questionnaire. Demographic information was collected and the students were asked to indicate their agreement with a set of seven statements using a modified Likert-type scale. The median total score was compared among different subgroups. Results: Fifty-eight of the 68 third semester and 72 of the 73 fourth semester students participated. Sixty-three of the 120 students (52.5%) were male. Indians, Nepalese and Sri Lankans were the major nationalities. The median total score was 24. No significant difference in the median total score was seen among different subgroups. Conclusion: The students were of the opinion that the situation depicted in the video is similar to that existing in South Asia and appreciated the session. The concept of rational use of medicines was reemphasized among future primary care physicians. The full text of this paper is available at Journal of Institute of Medicine website